COMPETITION FOR WATER RESOURCES - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Ampalu Bedasso, Adabba, Ethiopia: 'I have found Getting Africa hooked on fish farming to be a very important article. It hassaid a lot to teach some NGOs, whose unplanned and unstudied operations is damaging promising resources. Adabba(Ethiopia)...